Kenaf/basalt fiber-reinforced epoxy matrix hybrid composites: Current trends, challenges, and future prospects in advanced material development - Palanivendhan Murugadoss; Ashish Verma; Suhas Ballal; Vijay J. Upadhye; Krishna Kumar Shukla; Priyadarshi Das; Kamakshi Priya K (Results in Engineering)
This study aims to develop and evaluate hybrid polymer composites reinforced with kenaf and basalt fibers, focusing on enhancing mechanical strength, thermal stability, structural integrity, and antibacterial effectiveness. The primary objective is to investigate the synergistic effect of combining inorganic basalt fibers and natural kenaf fibers in an epoxy matrix, optimizing their performance for potential applications in durable and self-cleaning materials. The study examines key mechanical properties, revealing a tensile strength of 94.85 MPa, flexural strength of 98.26 MPa, and impact strength of 29.97 kJ/m², demonstrating the composite's capability to withstand substantial loads and impacts. Microstructural analysis using scanning electron microscopy confirmed that the basalt-dominant sample exhibited a well-organized fiber arrangement, excellent fiber-matrix adhesion, and minimal voids, whereas the kenaf-dominant sample displayed weaker interfacial bonding and higher void content. Thermal performance analysis indicated strong heat resistance, with the composite achieving a maximum thermal conductivity of 0.35 W/mK and a peak heat deflection temperature of 143 °C, confirming its stability under elevated temperatures. The coefficient of linear thermal expansion of 27 × 10⁻⁶/ °C ensured dimensional stability across varying thermal conditions. Additionally, the composite exhibited significant antibacterial activity, with a 36 mm inhibition zone against Staphylococcus aureus at 500 µg, surpassing the antibacterial efficacy of streptomycin at 34 mm with 25 µg. These findings demonstrate the composite's potential for high-performance applications requiring mechanical durability, thermal stability, and antibacterial properties, making it a strong alternate materials for use in automotive, aerospace, and self-cleaning surface applications.